FILAMIN A IN BREAST CANCER: FROM LITERATURE TO FUNCTIONAL INSIGHTS (European Journal of Histochemistry)
Breast cancer remains a major clinical challenge, particularly due to the poor prognosis associated with metastatic disease1. While early-stage tumors often respond to treatment, progression to metastasis significantly lowers survival rates, highlighting the need for novel therapeutic approaches2. Filamin A (FLNa), an actin binding protein, has been implicated in processes such as cell migration, adhesion, proliferation, and DNA repair. Its overexpression has been reported across various malignancies, including breast cancer, yet the precise role of FLNa in tumor progression remains incompletely understood3,4. In this study, we combined a comprehensive literature review with in silico analyses of available databases to evaluate FLNa expression patterns and their correlation with clinical outcomes. Furthermore, we conducted in vitro experiments using MCF-7 and MDA-MB-231 cell lines to investigate the functional role of FLNa in breast cancer-related processes. Our integrated approach aims to clarify FLNa’s contribution to breast cancer progression and assess its viability as a therapeutic target.